2009
DOI: 10.1002/jor.20897
|View full text |Cite
|
Sign up to set email alerts
|

Does loading influence the severity of cartilage degeneration in the canine Groove‐model of OA?

Abstract: Many animal models are used to study osteoarthritis (OA). In these models the role of joint loading in the development of OA is not fully understood. We studied the effect of loading on the development of OA in the canine Groove-model. In ten female beagle dogs OA was induced in one knee according to the Groove-model. The animals were divided in groups with and without forced-loading. Forced-loading was achieved by fixing the contra-lateral limb to the trunk 3 times a week for 4 hours. After 20 weeks joint tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…The surgically induced cartilage damage was restricted to a maximum of four grooves on femoral condyles only, whereas in the regularly performed Groove model OA at least 10 grooves are made 18. Additionally, loading of the joints was minimized, knowing that loading adds to development of OA 23. In the present study, the animals were permanently housed individually in indoor pens (3.5 m 2 ), the minimal reasonably acceptable space, to keep movement and with that loading of the joints to a minimum.…”
Section: Discussionmentioning
confidence: 99%
“…The surgically induced cartilage damage was restricted to a maximum of four grooves on femoral condyles only, whereas in the regularly performed Groove model OA at least 10 grooves are made 18. Additionally, loading of the joints was minimized, knowing that loading adds to development of OA 23. In the present study, the animals were permanently housed individually in indoor pens (3.5 m 2 ), the minimal reasonably acceptable space, to keep movement and with that loading of the joints to a minimum.…”
Section: Discussionmentioning
confidence: 99%
“…As such, subtly complex differences in joint geometry may not be detected and it may be these differences that contribute most to differences in mechanics that may lead to the development or progression of knee osteoarthritis. Numerous studies have demonstrated the role of mechanical loading factors in onset and advancement of OA (Andriacchi et al, 2004; Arokoski et al, 2000; Sharma et al, 1999; Vos et al, 2009; Yang et al, 2009), and clinical studies have demonstrated that joint incongruity is related to early cartilage degeneration (Harris, 1986; Hohe et al, 2002; Mankin et al, 1971). …”
Section: Discussionmentioning
confidence: 99%
“…Canine IVD tissue was collected from dogs euthanized in studies investigating osteoarthritis (Experiment numbers DEC 2007.III.08.110 and DEC 2009.III.05.037; euthanasia performed by way of an intravenous overdose of pentobarbital) [31-33] and cardiovascular disease (Experiment number DEC 2007.II.01.029; euthanasia performed under general anesthesia by way of fibrillation and subsequent excision of the heart) [[34], other, unpublished data].…”
Section: Methodsmentioning
confidence: 99%